2018
DOI: 10.1371/journal.pone.0202119
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic screening and molecular characterization of carbapenemase-producing Gram-negative bacilli recovered from febrile neutropenic pediatric cancer patients in Egypt

Abstract: AimInfections with carbapenem-resistant Gram-negative bacteria (GNB) are among the most frequent complications in the immunocompromised cancer patients because of their considerable morbidity and mortality. Therefore, the aim of the current study was to characterize the prevalence of carbapenemase-producing GNB recovered from febrile neutropenic pediatric cancer patients in Egypt.MethodsStandard methods were used for identification, sensitivity testing (Kirby-Bauer and broth microdilution method according to C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
36
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 32 publications
10
36
7
Order By: Relevance
“…In the same study, CTX-M type was the most common β-lactamase-encoding gene represent about 90% of the ESBL-producing E. coli [21] and this was higher than that in our study (20.41%). In contrast to this study, In a study conducted by Abdallah et al, the genetic analysis showed that CTX-M was present in 96% of ESBL E. coli in adult infections, also in a recent study the most common ESBLs genes detected were again CTX-M in multi-drug resistant gram negative bacilli in infected febrile neutropenic cancer patients [42]. These discrepancies can be attributed to the differences in age categories in the first study and the different patients' clinical criteria in the second one.…”
Section: Discussioncontrasting
confidence: 90%
“…In the same study, CTX-M type was the most common β-lactamase-encoding gene represent about 90% of the ESBL-producing E. coli [21] and this was higher than that in our study (20.41%). In contrast to this study, In a study conducted by Abdallah et al, the genetic analysis showed that CTX-M was present in 96% of ESBL E. coli in adult infections, also in a recent study the most common ESBLs genes detected were again CTX-M in multi-drug resistant gram negative bacilli in infected febrile neutropenic cancer patients [42]. These discrepancies can be attributed to the differences in age categories in the first study and the different patients' clinical criteria in the second one.…”
Section: Discussioncontrasting
confidence: 90%
“…The results shown in Table 1 indicate that in Egypt from 2000 through 2020, resistance to various cephalosporins, such as cefuroxime, cefotaxime, ceftazidime, and cefepime, was higher than that to b-lactam/b-lactamase inhibitor combinations, e.g., amoxicillin-clavulanic acid and piperacillin-tazobactam. A rise in resistance was reported against aminoglycosides; gentamcin/amikacin, ciprofloxacin (a quinolone drug) and carbapenems, i.e., imipenem and meropenem [ 84 , 85 , 86 , 87 , 88 , 89 ]. The increase in antibiotic resistance in these isolates has also been demonstrated by β-lactamase detection.…”
Section: Resultsmentioning
confidence: 99%
“…An increasing trend was also observed for bla PER and bla GES ESBL traits. On the other hand, bla VIM and bla IMP were the most prevalent metallo-β-lactamases resistance encoding genes which showed a remarkable increase, along with bla NDM [ 84 , 88 , 90 , 91 , 92 , 93 ].…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, out of the 342 GNB; 188 (54.9%) isolates were MDR which is in accordance with previous studies and imposes weak infection control strategies. 26 , 27 Despite the fact that the antibiogram analysis of recovered GNB is raising concerns, yet, the overall sensitivity patterns of amikacin, doxycycline and tigecycline ranging from 70% to 85% rise as a promising hope.…”
Section: Discussionmentioning
confidence: 99%